Produção de cintiladores cerâmicos de germanato de bismuto (Bi4Ge3O12) através da prensagem a quente - Matos, Ivus Lorenzo Oliveira (2018)
In the present work the potential of ceramic scintillator production of bismuth germanate by hot pressing was investigated. The microstructure and the scintillation yield were studied as function of the hot pressing parameters, such as time sintering plateau (4 and 10 hours), temperature (840 e 875 °C), and pressure (0.10, 0.14, and 0.18 MPa). Values of relative densities were obtained through Archimedes method showing that for the ceramic bodies produced the densities were higher than 94%. X-ray diffraction showed that the ceramics and the precursor powder exhibited two different Bi-Ge-O stoichiometries, the majority one Bi4Ge3O12 and the spurious one Bi12GeO20. Analyzes by scanning electron microscopy (SEM) was used to investigate the microstructure of the grains with the changes of hot pressing parameters. The optical characterization was done by radioluminescence (RL), in which it was verified that the sample sintered by hot pressing have better efficiency in the characteristic emission of BGO. The influence of sintering condition in scintillation efficiency of the ceramic bodies was also investigated.